2021
DOI: 10.1186/s13006-021-00408-x
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal administration of colostrum for preventing necrotizing enterocolitis and late-onset sepsis in preterm infants with gestational age ≤ 32 weeks: a pilot single-center randomized controlled trial

Abstract: Background Oropharyngeal administration of colostrum (OAC) may provide immunoprotective and anti-inflammatory effects that potentially reduce the incidence of necrotizing enterocolitis (NEC) and late-onset sepsis and improve short-term outcomes. Our objective was to evaluate the role of OAC in the early prevention of NEC and late-onset sepsis in preterm infants with gestational age (GA) ≤ 32 weeks. Methods A pilot, single-center, 1:1 parallel rando… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 44 publications
2
50
0
9
Order By: Relevance
“…Intraventricular hemorrhage is a common type of intracranial hemorrhage in preterm infants, and it is also one of the main causes of death and disability in preterm infants. In total, 4 studies ( 4 , 5 , 7 , 13 ) reported the incidence of IVH (grade ≥3) in 645 preterm infants ( Figure 11 ). The incidence of IVH in the colostrum group (grade ≥3) was 2.2% (7/315) and in the control group was 5.2% (17/330).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Intraventricular hemorrhage is a common type of intracranial hemorrhage in preterm infants, and it is also one of the main causes of death and disability in preterm infants. In total, 4 studies ( 4 , 5 , 7 , 13 ) reported the incidence of IVH (grade ≥3) in 645 preterm infants ( Figure 11 ). The incidence of IVH in the colostrum group (grade ≥3) was 2.2% (7/315) and in the control group was 5.2% (17/330).…”
Section: Resultsmentioning
confidence: 99%
“…The most serious outcome is PVL, which causes neurological sequelae in children. In total, 2 studies ( 5 , 8 ), with a total sample of 369 preterm infants, measured the incidence of PVL ( Figure 12 ). The incidence of PVL in the colostrum group was 1.1% (2/186) and in the control group was 1.6% (3/183).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations